Systematic review and meta-analysis of the efficacy and safety of chromium supplementation in diabetes - N. Suksomboon (2018)
What is known and objective Chromium is an essential mineral for carbohydrate and lipid metabolism. Results of previous systematic reviews and meta-analyses of chromium supplementation and metabolic profiles in diabetes have been inconsistent. Recently, several published trials have emerged. We conducted a systematic review and meta-analysis to assess the effects on metabolic profiles and safety of chromium supplementation in diabetes mellitus. Methods Clinical trials were identified through MEDLINE, the Cochrane library, CINAHL, Web of Science, Scopus and www.clinicaltrial.gov up to May 2013. Historical search of reference lists of related articles was also conducted. Studies were included if they (i) were randomized controlled trials comparing chromium mono- or combined supplementation against placebo, (ii) reported HbA1c or fasting plasma glucose and (iii) were of at least 3 weeks when reporting fasting plasma glucose, or of at least 8 weeks if HbA1c was reported. No language restriction was imposed. Treatment effect and adverse events were estimated with mean difference and odds ratio, respectively. Results and discussion Twenty-five randomized controlled trials met the inclusion criteria. Of these, 22 studies evaluated chromium monosupplementation. One study evaluated chromium yeast combined with vitamins C and E, and two others evaluated chromium picolinate plus biotin (CPB). Overall, chromium mono- and combined supplementation significantly improved glycaemic control (mean difference for HbA1c -0·55%; 95% CI -0·88 to -0·22%; P = 0·001, mean difference for FPG -1·15 mm; 95% CI -1·84 to -0·47 mm; P = 0·001). In particular, chromium monotherapy significantly reduced triglycerides and increased HDL-C levels. The effects on glucose and triglycerides levels were shown especially with chromium picolinate. Glycaemic control may improve with chromium monosupplementation of more than 200 μg daily. HbA1c and FPG also improved in patients with inadequate glycaemic control at baseline. The risk of adverse events did not differ between chromium and placebo. What is new and conclusions The available evidence suggests favourable effects of chromium supplementation on glycaemic control in patients with diabetes. Chromium monosupplement may additionally improve triglycerides and HDL-C levels. Chromium supplementation at usual doses does not increase the risk of adverse events compared with placebo. Data on chromium combined supplementation are limited and inconclusive. Long-term benefit and safety of chromium supplementation remain to be further investigated. Chromium supplementation improves glycaemic control in diabetes. © 2014 John Wiley & Sons Ltd.